2021
DOI: 10.3171/2020.12.spine20604
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes for late neurological deficits after long segment instrumentation for degenerative adult spinal deformity

Abstract: OBJECTIVE The most catastrophic symptom of proximal junctional failure (PJF) following long instrumented fusion surgery for adult spinal deformity (ASD) is neurological deficits. Although previous reports have shown that PJF usually developed during the early postoperative period, some patients showed late neurological deficits. The aim of this study was to report the incidence, characteristics, and surgical outcomes of PJF with late neurological deficits. METHODS Patients surgically treated for ASD at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Notably, upon undergoing revision surgery, a high incidence of perioperative complications was identified. 11 In a report, they had 85% of patient injury 'fall from height', and they had 55% of the fracture presentation at dorsal-lumbar junction (T12-L1). Burst-type morphology was reported in a maximum number of patients (65%).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, upon undergoing revision surgery, a high incidence of perioperative complications was identified. 11 In a report, they had 85% of patient injury 'fall from height', and they had 55% of the fracture presentation at dorsal-lumbar junction (T12-L1). Burst-type morphology was reported in a maximum number of patients (65%).…”
Section: Discussionmentioning
confidence: 99%
“…However, effective approaches to prevent UIVFs remain unclear. Strengthening bone density is considered an important measure,8,9 but some reports indicate that bone density and PJF are not related 5,10,11. Recently, Oe et al 12 named the ratio of pedicle screw (PS) length to the anterior-posterior diameter of the vertebral body at the UIV as the occupancy rate of a pedicle screw (ORPS) and, using finite element analysis, reported that the stress on the UIV decreased the most when the ORPS was 81.8% or more.…”
mentioning
confidence: 99%